A Pilot Study to Evaluate the Feasibility of the Image-Guided Breast Conserving Surgery in the Advanced Multimodality Image Guided Operating Suite (AMIGO) - Golshan, Mehra (Ann Surg Oncol, 2014)
BACKGROUND: The rate of re-excision in breast conserving surgery (BCS) remains high, leading to delay in initiation of adjuvant therapy, increased cost, increased complications and a negative psychological impact to the patient (1-3). We initiated a phase I clinical trial to determine the feasibility of using the intraoperative MRI to assess margins in the Advanced Multimodality Image Guided Operating (AMIGO) suite. METHODS: All patients received contrast-enhanced 3D MRI under general anesthesia in the supine position, followed by standard breast conserving therapy with or without wire guidance and sentinel node biopsy. Additional margin re-excision was performed of suspicious margins and correlated to final pathology (Figure 1). Feasibility was assessed in two components: (1) demonstration of safety & sterility and acceptable duration of the operation and imaging, (2) adequacy of intraoperative MRI imaging for interpretation and its comparison to final pathology. RESULTS: Eight patients (mean age: 48.5), 4 with stage I breast cancer and 4 with stage II breast cancers were recruited. All patients underwent successful breast conserving therapy in the AMIGO suite with no AMIGO-specific complications or break in sterility during surgery. The mean operative time was 113 minutes [93-146]. CONCLUSION: Our experience AMIGO suggests that it is feasible to use intraoperative MRI imaging to evaluate margin assessment in real time. Further research is required to identify modalities that will lead to reduction in re-excision in breast cancer therapy.